Pembingkaian Berita Pemberhentian Pegawai KPK pada Media Online detik.com dan tempo.co Periode 13-30 September 2021 - Karmudi Karmudi; Catur Suratnoaji (Universitas Merdeka Malang, 2022)
This research discusses the analysis of news framing of the dismissal of Komisi Pemberantasan Korupsi (KPK) on online media Detik.com and Tempo.co for the period 13-30 September 2021. The KPK dismissed as many as 57 of its employees in the process of changing employee status through Decree Number 1354, Chairman of the KPK Firli Bahuri still issued the decree even though in the implementation of the assessment there were findings of human rights violations and procedures based on the findings of Ombudsman RI and Komnas HAM. Researchers took data from 10 news texts published by Detik.com and Tempo.co for analysis using descriptive qualitative research and constructivist paradigms withRobert N. Entman's framing analysis method which focused on four analytical tools, namely problem definition, determining the cause of the problem, moral decisions, problem-solving. The results of this study indicate that Detik.com and Tempo.co have different news frames regarding the dismissal of KPK employees. Detik.com tends to corner the dismissed employee by citing dismissal as the impact of employees who do not meet the requirements in the assessment of the transfer of employee status to state civil servants, while Tempo.co tends to support dismissed employees by saying that the transfer of employee status is just an effort by the KPK to get rid of certain employees.Keywords: Framing, Employee Dismissal, KPK